1999
DOI: 10.1037/0022-006x.67.5.688
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the unmotivated in treatment for alcohol problems: A comparison of three strategies for intervention through family members.

Abstract: In a randomized clinical trial, 130 concerned significant others (CSOs) were offered 1 of 3 different counseling approaches: (a) an Al-Anon facilitation therapy designed to encourage involvement in the 12-step program, (b) a Johnson Institute intervention to prepare for a confrontational family meeting, or (c) a community reinforcement and family training (CRAFT) approach teaching behavior change skills to use at home. All were manual-guided, with 12 hr of contact. Follow-up interviews continued for 12 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
241
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(264 citation statements)
references
References 33 publications
14
241
2
7
Order By: Relevance
“…Results showed the effectiveness of the two methods in improving the quality of life but both CRAFT and Nar-Anon were not effective in reducing the depression of family members of substance abusers This is consistent with the results of the improving the quality of life and inconsistent with the studies by Christo and Sutton (1994), Meyers et al (1998), Miller et al (1999, Richter et al (2000), Gilachen (2006) and Kanz (2009). They showed that people who participated in CRAFT and Nar-Anon showed higher interest in life and decreased depression, anxiety, hostility, improved physical and mental health compared to those who did not participate.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Results showed the effectiveness of the two methods in improving the quality of life but both CRAFT and Nar-Anon were not effective in reducing the depression of family members of substance abusers This is consistent with the results of the improving the quality of life and inconsistent with the studies by Christo and Sutton (1994), Meyers et al (1998), Miller et al (1999, Richter et al (2000), Gilachen (2006) and Kanz (2009). They showed that people who participated in CRAFT and Nar-Anon showed higher interest in life and decreased depression, anxiety, hostility, improved physical and mental health compared to those who did not participate.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, Waller and Mahoney study the changes in family role and mental status of the family members of substance abusers, too. Miller et al (1999) showed that attending in the treatment sessions has useful effects on the performance and quality of life of the relatives of the drug abusers. For inconsistent results, it can be said that this study investigated the decreasing the depression of family members of substance abusers from different aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Research needs to examine the impact of parent and family-focused interventions when MR and substance abuse are present; results from studies conducted on similar interventions with non-MR populations have indicated improvements in participant psychosocial functioning, the substance abuser's level of use, and the substance abuser's willingness to enter treatment [e.g., Miller et al, 1999;McGillicuddy et al, 2001]. It may be through these kinds of interventions that family members of persons with MR will develop the skills to provide support to someone struggling with substance abuse [e.g., Watson et al, 1998].…”
Section: Future Research Needsmentioning
confidence: 99%
“…Members attribute improved psychological health (less depression, anger) and relationship and family satisfaction to Al-Anon attendance (Cutter and Cutter, 1987;Dittrich and Trapold, 1984;Keinz et al, 1995;Miller et al, 1999). Al-Anon may help COs cope more adaptively with the loved one's drinking and with life stressors related or unrelated to the drinking (Gorman and Rooney, 1979;McGregor, 1990;O'Farrell and Fals-Stewart, 2001).…”
Section: Al-anon Membersmentioning
confidence: 99%
“…Al-Anon Family Groups (Al-Anon), 12-step mutual-help groups for families and friends of problem-drinking individuals, offer help to deal with the impact of another's drinking. Al-Anon is the most widely used form of help for COs in the United States (Miller et al, 1999;O'Farrell and Clements, 2012;O'Farrell and FalsStewart, 2001). Of approximately 24,000 Al-Anon groups in more than 130 countries, approximately 14,000 are in the United States and Canada (http://www.al-anon.alateen.org).…”
mentioning
confidence: 99%